The changing use of executive recruitment consultancies: 1989-1993 - CLARK, Timothy Adrian Robert (Institutional Knowledge at Singapore Management University, 1994)
Organizations of all kinds are increasingly turning to external consultants for assistance with many aspects of management. This is a growing trend that shows no sign of weakening despite the recent recession. Indeed, consultants have become an indispensable part of management by providing specialist expertise that may not exist within their client organizations. This article examines the use of executive recruitment consultancies by corporate personnel managers in 53 organizations at two time points. Although it is concerned with one particular activity - executive recruitments - the analysis has implications for the use of consultants more generally.